The five dysfunctions of a team : a leadership fable - Lencioni, Patrick, 1965- 4 0 16; 5 (San Francisco, California : Jossey-Bass Publishers, 2002)
Exposes five dysfunctions that can cause work teams to struggle through a leadership fable in which Kathryn Petersen, new CEO at DecisionTech, begins to doubt the wisdom of having come out of retirement when she encounters chaos and challenges at every turn.
Adult.
Keywords: 2 -- 0; 6; Teams in the workplace. -- 20; 20; 2